Warthin-like Mucoepidermoid Carcinoma: A Combined Study of Fluorescence In Situ Hybridization and Whole-slide Imaging. (November 2015) - Ishibashi, Kenichiro; Ito, Yohei; Masaki, Ayako; Fujii, Kana; Beppu, Shintaro; Sakakibara, Takeo; Takino, Hisashi; Takase, Hiroshi; Ijichi, Kei; Shimozato, Kazuo; Inagaki, Hiroshi
Abstract : There has been some debate as to whether a subset of metaplastic Warthin tumors (mWTs) harbor the mucoepidermoid carcinoma (MEC)-associated CRTC1-MAML2 fusion. We analyzed 15 tumors originally diagnosed as mWT (mWT-like tumors), 2 of which had concurrent MECs. We looked for the CRTC1/3-MAML2 fusion transcripts and performed immunohistochemistry for p63 and fluorescence in situ hybridization (FISH) for the MAML2 split. To localize MAML2 split–positive cells at the cellular level, whole tumor tissue sections were digitalized (whole-slide imaging [WSI]). The CRTC1-MAML2, but not CRTC3-MAML2 was detected in 5/15 mWT-like tumors. FISH-WSI results showed that all epithelial cells harbored the MAML2 split in fusion-positive mWT-like tumors and were totally negative in fusion-negative mWT-like tumors. A review of the hematoxylin and eosin–stained slides showed that morphology of the "metaplastic" epithelium was virtually indistinguishable between fusion-positive and fusion-negative tumors. However, oncocytic bilayered tumor epithelium, characteristic to typical WT, was always found somewhere in the fusion-negative tumors but not in the fusion-positive tumors. This distinguishing histologic finding enabled 5 pathologists to easily differentiate the 2 tumor groups with 100% accuracy. The age and sex distribution of fusion-positive mWT-like tumor cases was similar to that of fusion-positive MEC cases and significantly different from those of fusion-negative mWT-like tumor and typical WT cases. In addition, only fusion-positive mWT-like tumors possessed concurrent low-grade MECs. In conclusion, a subset of mWT-like tumors were positive for the CRTC1-MAML2 fusion and had many features that are more in accord with MEC than with WT. The term Warthin-like MEC should be considered for fusion-positive mWT-like tumors.